2023
DOI: 10.1021/acscatal.3c01942
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Photoredox/Nickel/Halide Catalysis for the Phosphorylation of Alcohols with White Phosphorus

Abstract: Dialkyl phosphites (DAPIs) are important precursors in the formation of phosphorus−carbon and phosphorus− heteroatom bonds with significant industrial applications. Traditional PCl 3 -based procedures suffer from high waste production and toxic reaction conditions. The direct conversion of white phosphorus (P 4 ) to DAPIs can circumvent these issues by avoiding the use of Cl 2 and PCl 3 . We present a waste-free, environmentally friendly approach for synthesizing DAPIs using P 4 and alcohols, leveraging a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Very recently, Tang and co-workers developed a photoredox-catalyzed direct phosphorylation of alcohols with P 4 to access DAPIs and TAPAs through a synergistic catalysis of organic dye photocatalyst, nickel catalyst, and halide anion (Scheme 6). [30] The reaction generality testing demonstrated that a wide range of substituted alcohols bearing electronwithdrawing or sterically hindered groups are compatible with slightly modified conditions. The fluorescence quenching experiment on organic dye photocatalyst, Rhodamine-6G, observed an obvious fluorescence decline in a KI concentration-dependent manner, implying a SET behavior from the photoexcited state of Rhodamine-6G to halide anion.…”
Section: Photophosphorylation Of Alcohols With Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Tang and co-workers developed a photoredox-catalyzed direct phosphorylation of alcohols with P 4 to access DAPIs and TAPAs through a synergistic catalysis of organic dye photocatalyst, nickel catalyst, and halide anion (Scheme 6). [30] The reaction generality testing demonstrated that a wide range of substituted alcohols bearing electronwithdrawing or sterically hindered groups are compatible with slightly modified conditions. The fluorescence quenching experiment on organic dye photocatalyst, Rhodamine-6G, observed an obvious fluorescence decline in a KI concentration-dependent manner, implying a SET behavior from the photoexcited state of Rhodamine-6G to halide anion.…”
Section: Photophosphorylation Of Alcohols With Pmentioning
confidence: 99%
“…As the expansion of former photo-phosphorylation of alcohols, thiophenols were amenable to the addition to P 4 to afford some phosphorotrithioate products (Scheme 7B). [30] While neither of the above work provides the explicit mechanism, it is speculated that the reaction occurred through the manipulation of sulfur-centered free radicals. However, the substrate scope is strictly restricted to thiophenols, whereas alkyl thiols cannot participate in the reaction.…”
Section: Photophosphorylation Of Thiophenols With Pmentioning
confidence: 99%
“…[21][22][23][24][25] However, to the best of our knowledge, direct functionalization of P 4 for the synthesis of phosphorothioates has not been reported in the literature due to the challenge of cleaving all six P-P bonds of the P 4 tetrahedron and orderly installing different atoms at phosphorus center. [26][27][28][29][30][31][32] As a continuum of our efforts in developing green methodologies for the selective transformation of P 4 into useful P 1 products without hazardous chlorination steps, [33][34][35][36][37] we report the first copper-catalyzed three-component coupling reaction of P 4 , alcohols, and aryl disulfides for the synthesis of phosphorothioates under mild conditions, exhibiting high phosphorus conversion (Scheme 1e).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, methods for the synthesis of organophosphorothioates mainly rely on the formation of the P–S or C–S bonds through substitution reactions, cross-coupling reactions, and radical-based reactions . In recent years, Ir or Cu catalysts showed their uniqueness in chemical bond activation and were proven to be successful for realizing various challenging chemical reactions .…”
Section: Introductionmentioning
confidence: 99%